Penyelesaian Tindak Pidana Kesusilaan Antar Anak Dengan Pendekatan Restorative Justice - Kustrini, Kustrini; , Prof. Dr. Supanto S.H; , Dr. Natangsa Surbakti, S.H., M.Hum (2015)
The children are potential to development and growth to future of country or the other word the children are next generation of country. They must be attention serious from family, society and country and notion. Good or bad of country future determine from the young generation or the children. The children characteristic influences environment, so it cause error action so the action to criminal. To problem solving is special action or restorative justice. Sanction to the children are not same with adult people but with building that education characteristic.